Analisis Penerapan Metode Economic Order Quantity Sebagai Upaya Pengendalian Persediaan Bahan Baku Pada UD Imanuel Tompaso Baru - Susanti; Meily Y. B. Kalalo (Yayasan Widyantara Nawasena Raharja, 2023)
Economic Order Quantity is a method for determining the optimal purchase quantity so that there is no excess or shortage of raw materials. The aim of this research is to see how the Economic Order Quantity method is applied as an effort to control raw material supplies. The type of research used is descriptive qualitative. The research results show that there are quite large differences in the number of purchases, purchase time, and total inventory costs using the company's own method and the application of the Economic Order Quantity method. The number of purchases of raw materials according to the company is greater than using the Economic Order Quantity method, the company's purchasing frequency is more frequent than using the Economic Order Quantity method and there is a large comparison of total inventory costs. Therefore, it is hoped that companies can apply the Economic Order Quantity method to determine the optimal purchase quantity. The right repurchase time and at the same time can reduce total inventory costs.